Room- and low-temperature transmission of diffusion-doped Fe2+ : ZnSe polycrystal at 2940 nm. (March 2017) - Il'ichev, N.N.; Bufetova, G.A.; Gulyamova, E.S.; Pashinin, P.P.; Sidorin, A.V.; Polyanskii, V.I.; Kalinushkin, V.P.; Gavrishchuk, E.M.; Ikonnikov, V.B.; Savin, D.V.
Abstract: Transmission of a polycrystalline Fe 2+ : ZnSe sample during irradiation by a pulsed Er 3+ : YAG laser with a wavelength of 2940 nm is measured at low and room temperatures. It is found that the sample in a strong field (energy density 1.3 J cm –2, laser pulse duration 320 ns, peak intensity 4.1 MW cm –2 ) is bleached almost completely at both low and room temperatures. The temperature dependence of transmission is measured in the range of 105 – 273 K in weak and strong fields.